Implementation of Spatial Multi-Criteria Analysis Method For Flood Vulnerability Mapping in Banjarmasin City - Wisnu Putra Danarto; Ghinia Anastasia Muhtar; Selamat Riadi (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
Flooding is the most prevalent type of natural disaster in terms of both frequency and historical impact in Banjarmasin City. A flood risk assessment is imperative as a foundation for various risk reduction activities (in the pre-disaster stage) and mitigation measures (in the post-disaster stage). This study aims to conduct an analysis of flood hazard risk by presenting its spatial distribution throughout Banjarmasin City. The analysis was conducted utilizing the Spatial Multi-Criteria Analysis (SMCA) method, whereby the spatial distribution of flood hazard risk is determined by the factors (criteria) that influence it, with these factors assigned weights according to their influence on the analysis outcomes. The criteria considered for determining the flood hazard risk in Banjarmasin City include land cover, topography, flow density, distance from rivers, and slope gradient. Prior to processing via the Geographic Information System platform, these criteria undergo a ranking and weighting process facilitated by the Spatial-Analytical Hierarchy Process (Spatial-AHP). The results of the analysis indicate that land cover is the most significant factor, with a weight of 0.48. Other criteria, including topography, flow density, distance from the river, and slope, were also considered. The spatial analysis and mapping results have produced a flood risk index, with a distribution of very high and high risk classes that are dominant in the North Banjarmasin, Central Banjarmasin, and West Banjarmasin Districts. In contrast, South Banjarmasin has a dominant high and moderate class, and East Banjarmasin is a district with a relatively lower hazard risk class compared to other districts. Several key factors contribute to this phenomenon. Firstly, the area's topographic features, located below sea level, trap water, especially during extended periods of heavy rainfall. Second, the city of Banjarmasin is located in the downstream area, which is the confluence of several rivers that carry water from upstream, and this situation is exacerbated by heavy rainfall. Thirdly, the presence of closed land cover, defined by dense vegetation and impermeable soil, intensifies the risk of flooding.